Metal organic framework adsorbing material as well as preparation method and application thereof
The metal organic frame adsorption material prepared by solvothermal reaction uses specific pocket capture channels to solve the problem of insufficient capacity and selectivity of existing adsorbents, and achieve efficient and selective antimony removal.
Patent Information
- Application Number
- CN202411787897.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-06
- Publication Date
- 2025-02-07
- Estimated Expiration
- 2044-12-06
AI Technical Summary
When removing antimony from water, the capacity and selectivity of the existing adsorbents are insufficient, and it is difficult for the preparation method to improve capacity and selectivity at the same time.
Using soluble bismuth salt as the metal source and phenylatic acid as the linking ligand, metal organic frame adsorption material is prepared through solvothermal reaction to form a material with specific pocket capture pores.
Efficient and selective capture of Sb(OH)6- in water is achieved, significantly improving adsorption capacity and selectivity, and the distribution coefficient reaches 1.1×104mL g-1.
Smart Images

Figure CN119391000A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of adsorbent material preparation, and in particular to a metal organic framework adsorption material and a preparation method and application thereof. Background Art
[0002] Excessive mining and smelting of antimony ore have resulted in a large amount of antimony being released into the water environment, with antimony concentrations as high as 1330μg / L to 7000μg / L. The "Sanitary Standards for Drinking Water" clearly stipulates that the concentration of antimony in drinking water shall not exceed 5μg / L. These antimony-containing wastewaters not only threaten human life and safety, but also cause a huge waste of resources. Therefore, it is necessary to effectively remove antimony from wastewater.
[0003] Antimony in water is mainly present as pentavalent oxygen-containing anions Sb(OH) 6- The precipitation method has a dominant position in the early stage of the development of antimony removal from water bodies. It has the advantages of simple process and convenient operation, but the large-scale use of precipitants and sediment treatment processes are typical high-carbon emission and high-energy consumption processes, and a single technical means cannot achieve complete removal of antimony. In comparison, the ion exchange method has a higher and faster removal efficiency, but the ion resin is expensive and easily oxidized and reduced to lose its effect, making it difficult to be widely used. The adsorption method is currently an effective and feasible method for treating antimony-containing heavy metal wastewater due to its advantages such as simple operation, green environmental protection and high efficiency.
[0004] To achieve the resource recovery of heavy metals, the high capacity and selectivity of adsorption materials must be solved. The commonly used adsorbents reported so far include activated carbon, zeolite, metal oxides, etc., but they usually have low specific surface area, small pore volume, and few active functional groups, resulting in low adsorption capacity and poor selectivity.
[0005] Existing methods for preparing adsorbents mainly focus on increasing the specific surface area and modifying different functional groups to improve adsorption capacity. However, increasing the specific surface area is difficult to improve the adsorption capacity, while modifying different functional groups sharply reduces the selectivity of the material and cannot ensure complete access to effective sites. Summary of the invention
[0006] In view of the deficiencies of the above-mentioned prior art, the object of the present invention is to provide a metal organic framework adsorption material and a preparation method and application thereof. The present invention uses a soluble bismuth salt as a metal source and trimesic acid as a connecting ligand to prepare a metal organic framework adsorption material with specific pocket-type capture channels through a solvent thermal reaction.
[0007] In order to solve the above technical problems, the present invention adopts the following technical solutions:
[0008] A method for preparing a metal organic framework adsorption material comprises the following steps:
[0009] In an organic solvent, a metal-organic framework adsorption material with specific pocket-type capture channels was prepared by solvothermal reaction using soluble bismuth salt as the metal source and trimesic acid as the connecting ligand.
[0010] The present invention uses soluble bismuth salt as a metal source and trimesic acid as a connecting ligand to prepare a metal organic framework adsorbent material with specific pocket-type capture channels through a solvent thermal reaction. The porous organic framework adsorbent formed by the present invention has a high charge density of cationic Bi 3+ The high coordination number and flexible coordination mode of the metal organic framework adsorption material have the ability to match Sb(OH) 6- The pore structure of the size is conducive to Sb(OH) 6- The metal organic framework adsorption material with a high proportion of open pocket capture channels is developed based on the inherent structural properties of the material itself to form Bi-O-Sb bonds and be selectively captured. 6- Targeted capture to achieve a dual improvement in adsorption capacity and selectivity.
[0011] In a preferred embodiment of the present invention, the mass ratio of the soluble bismuth salt to trimesic acid is 1:1-5.
[0012] In a preferred embodiment of the present invention, the solvent thermal reaction temperature is 120° C. to 200° C., and the reaction time is 12 h to 72 h.
[0013] In a preferred embodiment of the present invention, the organic solvent is a mixed solvent of N,N-dimethylformamide and methanol.
[0014] In a preferred embodiment of the present invention, in the mixed solvent, the volume ratio of N,N-dimethylformamide to methanol is 1 to 4:1.
[0015] In a preferred embodiment of the present invention, the soluble bismuth salt is Bi(NO3)3·5H2O.
[0016] Another object of the present invention is to provide a metal organic framework adsorption material prepared by any of the preparation methods described above.
[0017] In a preferred embodiment of the present invention, the metal organic framework adsorption material is a hexagonal rod-shaped structure.
[0018] The third object of the present invention is to provide a metal organic framework adsorption material as described above for efficiently and selectively capturing Sb(OH) in antimony-containing wastewater. 6- Application in.
[0019] In a preferred embodiment of the present invention, the concentration of antimony-containing wastewater is 50 mg / L to 2000 mg / L, and the usage ratio of the metal organic framework adsorption material to the antimony-containing wastewater is 1 mg: 1 mL to 4 mL.
[0020] Compared with the prior art, the present invention has the following beneficial effects:
[0021] 1. The present invention uses soluble bismuth salt as a metal source and trimesic acid as a connecting ligand to prepare a metal organic framework adsorbent material with specific pocket-type capture channels through a solvent thermal reaction. The porous organic framework adsorbent formed by the method of the present invention has a high charge density of cationic Bi 3+ The high coordination number and flexible coordination mode of the metal organic framework adsorption material have the ability to match Sb(OH) 6- The pore structure of the size is conducive to Sb(OH) 6- The metal organic framework adsorbent with open pockets is developed based on the inherent structural properties of the material itself to form Bi-O-Sb bonds at the active sites of the adsorbent material, which is used for Sb(OH) 6- Targeted capture to achieve a dual improvement in adsorption capacity and selectivity.
[0022] 2. The good adsorption performance of the metal organic framework adsorption material prepared by the present invention is mainly due to the following points: ① The metal organic framework adsorption material has a large specific surface area and can provide enough adsorption sites; ② The large number of pores inside the material provide enough transmission channels, which is conducive to Sb(OH) 6- Mass transfer rate increases the accessibility of active sites, resulting in increased adsorption capacity; ③ Open channels and Sb(OH)6 - The size is appropriately matched and selectively captured by forming Bi-O-Sb bonds. Based on this, this high affinity for Sb(OH) 6- The distribution coefficient reaches 1.1×10 4 mL g -1 , which is significantly higher than the distribution coefficient of other coexisting ions, showing high selectivity. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1 This is a diagram of the preparation process of Example 1 of the present invention.
[0024] Figure 2 This is a SEM image of the metal organic framework adsorption material prepared in Example 1 of the present invention.
[0025] Figure 3 This is an isothermal adsorption curve diagram of the metal organic framework adsorption material prepared in Example 1 of the present invention.
[0026] Figure 4 This is a graph showing the effect of adsorption temperature on the adsorption capacity of the metal organic framework adsorption material prepared in Example 1.
[0027] Figure 5 This is a graph showing the effect of different pH values on the adsorption performance of the metal organic framework adsorption material prepared in Example 1.
[0028] Figure 6 This is a diagram showing the influence of the affinity of coexisting ions on the metal organic framework adsorption material prepared in Example 1.
[0029] Figure 7 In the figure, (a) is a schematic diagram of treating antimony-containing aqueous solution with a single metal organic framework adsorption material fixed bed; (b) is an adsorption breakthrough curve of a single metal organic framework adsorption material fixed bed; (c) is an analysis curve of a single metal organic framework adsorption material fixed bed.
[0030] Figure 8 In the figure, (a) is a schematic diagram of treating antimony-containing aqueous solution by connecting three metal organic framework material fixed beds in series; (b) is an adsorption breakthrough curve diagram of three metal organic framework material fixed beds in series; (c) is an analysis curve diagram of three metal organic framework adsorption material fixed beds in series. DETAILED DESCRIPTION
[0031] The following is a detailed description of the technical solutions in the embodiments of the present invention in combination with the preferred embodiments and the accompanying drawings. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0032] It should be noted that all professional terms used in the present invention are only for the purpose of describing specific embodiments and are not intended to limit the scope of protection of the present invention. Unless otherwise specifically stated, various raw materials, reagents, instruments and equipment used in the following embodiments of the present invention can be purchased from the market or prepared by existing methods.
[0033] Example 1
[0034] A method for preparing a metal organic framework adsorption material comprises the following steps:
[0035] (1) Weigh 50 mg of Bi(NO3)3·5H2O and dissolve it in a beaker containing 50 mL of a 1:1 volume ratio N,N-dimethylformamide and methanol mixed solution, and ultrasonicate and magnetically stir for 10 min to form a dispersed solution.
[0036] (2) Then, 150 mg of trimesic acid was added thereto and mixed thoroughly. The mixture was then ultrasonically treated for 10 minutes to make the solution a colorless, transparent and uniform mixture.
[0037] (3) The colorless and transparent mixed solution was transferred to a 100 mL stainless steel reactor lined with polytetrafluoroethylene for solvothermal reaction at a constant temperature of 180° C. for 24 h.
[0038] (4) After the reaction is completed, the reactor is cooled naturally at room temperature, the obtained product is centrifuged, and then washed three times with N,N-dimethylformamide, methanol and water respectively, and finally placed in a vacuum drying oven at 120°C for 24 hours. The obtained dry white powder is the metal organic framework adsorption material. The preparation process is as follows: Figure 1 shown.
[0039] Example 2
[0040] A method for preparing a metal organic framework adsorption material comprises the following steps:
[0041] (1) Weigh 50 mg of Bi(NO3)3·5H2O and dissolve it in a beaker containing 50 mL of a mixed solution of N,N-dimethylformamide and methanol in a volume ratio of 2:1. Ultrasonicate and magnetically stir for 10 min to form a dispersed solution.
[0042] (2) Then, 50 mg of trimesic acid was added thereto and mixed thoroughly. The mixture was then ultrasonically treated for 10 minutes to make the solution a colorless, transparent and uniform mixture.
[0043] (3) The colorless and transparent mixed solution was transferred to a 100 mL stainless steel reactor lined with polytetrafluoroethylene for solvothermal reaction at a constant temperature of 120° C. for 72 h.
[0044] (4) After the reaction is completed, the reactor is naturally cooled at room temperature, the product is centrifuged, and then washed three times with N,N-dimethylformamide, methanol and water respectively, and finally placed in a vacuum drying oven at 120°C for 24 hours. The obtained dry white powder is the metal organic framework adsorption material.
[0045] Example 3
[0046] A method for preparing a metal organic framework adsorption material comprises the following steps:
[0047] (1) Weigh 50 mg of Bi(NO3)3·5H2O and dissolve it in a beaker containing 50 mL of a mixed solution of N,N-dimethylformamide and methanol in a volume ratio of 4:1. Ultrasonicate and magnetically stir for 10 min to form a dispersed solution.
[0048] (2) Then, 250 mg of trimesic acid was added thereto and mixed thoroughly. The mixture was then ultrasonically treated for 10 minutes to make the solution a colorless, transparent and uniform mixture.
[0049] (3) The colorless and transparent mixed solution was transferred to a 100 mL stainless steel reactor lined with polytetrafluoroethylene for solvothermal reaction at a constant temperature of 200° C. for 12 h.
[0050] (4) After the reaction is completed, the reactor is naturally cooled at room temperature, the product is centrifuged, and then washed three times with N,N-dimethylformamide, methanol and water respectively, and finally placed in a vacuum drying oven at 120°C for 24 hours. The obtained dry white powder is the metal organic framework adsorption material.
[0051] Results Analysis
[0052] Figure 2 This is a SEM image of the metal organic framework adsorbent prepared in Example 1 of the present invention. The SEM image clearly shows that the metal organic framework adsorbent has a regular hexagonal rod structure with a very smooth surface. Its diameter is about 0.8 μm and its length is 4 μm. The hexagonal structure of the adsorbent of the present invention is mainly due to the high charge density of the cation Bi 3+ The high coordination number and flexible coordination mode form a strong coordination mode with the rigid ligand trimesic acid, and form a periodic and orderly arranged coordination network combination mode through self-assembly linking. The 9 metal coordination centers Bi 3+ , the 9 carboxyl ligand units of trimesic acid and the 9 coordinated water molecules constitute a repeating structural unit, each Bi 3+ The ion will bind to the two adjacent Bi 3+ By sharing the O atoms on the four carboxyl ligand units, these repeated structural units form a hexagonal prism structure with open pores.
[0053] Pentavalent antimony solution was prepared by dissolving potassium pyroantimonate in ultrapure water. 5.398 g KSbO6H6 was dissolved in 1 L of ultrapure water by ultrasonication to prepare 2.5 g L -1 Sb(OH) 6- The stock solution was prepared by diluting the stock solution to the Sb(OH) 6-Concentration, determination of Sb(OH) in water samples using continuous light source atomic absorption spectrometer 6- concentration, used to evaluate the metal organic framework adsorbent for Sb(OH) 6- All experiments in the present invention were carried out three times, and the final data is the average value of the three experiments.
[0054] 20 mg of the metal organic framework adsorption material prepared in Example 1 was added to 20 mL of Sb(OH) 6- The solution was oscillated in a constant temperature oscillator at 318K for 12 h with the rotation speed set at 180 rpm. The initial concentration of the adsorption solution was 50 mg L -1 , 100mg L -1 , 300mg L -1 , 500mg L -1 , 800mg L -1 , 1000mg L -1 , 1200mg L -1 , 1400mg L -1 , 1600mgL -1 After adsorption equilibrium, the sample was filtered through a 0.45 μm polyethersulfone membrane to obtain the supernatant, Sb(OH) 6- The concentration changes before and after adsorption were measured using a ContrAA 700 high-resolution continuous source atomic absorption spectrometer. Figure 3 This is the isothermal adsorption curve of the metal organic framework adsorption material prepared in Example 1 of the present invention. The results show that the metal organic framework adsorption material has an adsorption capacity of Sb(OH) 6- The maximum adsorption capacity of ions Q max It is 850 mg / g, showing an ultra-high adsorption capacity.
[0055] 20 mg of metal organic framework adsorbent was added into 20 mL of Sb(OH) 6- The solution was oscillated in a thermostatic incubator at 288K, 303K and 318K for 12 h, with the rotation speed set at 180 rpm. The initial concentration of the adsorption solution was 50 mg L -1 ~2500mg L -1 After adsorption equilibrium, the sample was taken out and filtered through a 0.45 μm polyethersulfone membrane to obtain the supernatant. Sb(OH) 6- The concentration changes before and after adsorption were measured using a ContrAA 700 high-resolution continuous source atomic absorption spectrometer. Figure 4 The effect of adsorption temperature on the adsorption capacity of the metal organic framework adsorption material prepared in Example 1 shows that the metal organic framework adsorption material has a good adsorption capacity for Sb(OH)6 -The adsorption of ions increases with increasing temperature.
[0056] Prepare 5 50 mL volumes with an initial concentration of 200 mg L -1 Sb(OH)6 - Solution, Sb(OH)6 - The pH range of the solution was adjusted to 1-11. - 50 mg of the metal organic framework adsorption material of the present invention was added to the solution. The solution was shaken in a constant temperature oscillating box at 303 K for 2 h. After adsorption equilibrium, the supernatant solution was collected by filtering through a pinhole filter membrane. The Sb(OH)6 - The concentration was measured using a ContrAA 700 high-resolution continuous source atomic absorption spectrometer. Figure 5 The results show that the metal organic framework adsorption material has a strong acid and base effect on Sb(OH)6 - The ions are still well adsorbed, the adsorption material is resistant to strong acids and alkalis, and has a wide range of adsorption applications.
[0057] Selective adsorption: 50 mg of metal organic framework adsorbent was added to 50 mL of Sb(OH)6 - ,As(V),PO4 3- , SO4 2- , NO 3- , Cl - , Zn 2+ ,Co 2+ , Ni 2+ and Cd 2+ The ion concentration was 200 μg / L -1 The mixed solution was shaken in a 30°C constant temperature shaker for 12 hours. After adsorption equilibrium, the supernatant was collected by pinhole filtration. The concentration of each component ion in the supernatant was determined using a ContrAA 700 high-resolution continuous light source atomic absorption spectrometer and ion chromatography. The results are shown in Figure 6 As shown in the figure, it can be seen that the metal organic framework adsorption material can absorb Sb(OH) 6- The selective separation of Sb(OH) and other metal ions indicates that the metal organic framework adsorbent of the present invention is effective in the adsorption of Sb(OH) 6- Has excellent selectivity.
[0058] Practical Application
[0059] (1) Short-term fixed bed of single metal organic framework adsorbent
[0060] The operation time and working efficiency of the fixed bed adsorption have always been a very important issue in engineering applications.6- When treating wastewater, the adsorption fixed bed should be reasonably designed and arranged to promote Sb(OH) 6- Capture of. Figure 7 (a) is a schematic diagram of a single metal organic framework adsorption material fixed bed treating an antimony-containing aqueous solution. A QP-01 vacuum pump is used to provide power support for the flow system. The diameter of the PVC adsorption column is 1.3 cm and the height is 6 cm. The filling height of the metal organic framework adsorption material in the adsorption column is 1.1 cm, and the mass of the filled metal organic framework adsorption material is 0.3 g. Total organic carbon in tap water = 0.41 mg L -1 , pH = 7.24. Sb(OH) added to tap water 6- The initial concentration of the solution C0 is 200 μg L -1 ,Sb(OH) 6- Solution at 1.93 cm min -1 The adsorption was carried out through the adsorption column at a loading flow rate of , and the empty bed contact time EBCT of a single column was 0.570min. Adsorption of Sb(OH) 6- After completion, at 1.1 mL / min -1 The adsorption column was analyzed with a flow rate of 0.1 M HCl as eluent.
[0061] In fixed bed experiments, the effluent was collected in aliquots at a minimum of 30 mL of sample effluent for analysis, which is approximately 20 bed volumes. Figure 7 As shown in (b), rapid adsorption breakthrough occurs in a single fixed bed with an initial concentration of 200 μg L -1 , the flow rate is 1.93 cm / min, the empty bed contact time is 0.570 min, when the concentration of the effluent reaches Sb(OH) 6- The maximum contaminant concentration allowed in drinking water is 6 μg L -1 , that is, when the absorption breakthrough point C / C0 = 0.03, a single metal organic framework adsorption material fixed bed can process Sb(OH) 6- The volume is about 1260 BV, or 1838 mL. At the point of complete adsorption saturation, i.e., exhaustion point C / C0=0.95, the volume that can be processed by a single adsorption fixed bed is about 2037 BV, or 2972 mL. Sb(OH) 6- The adsorption breakthrough curve is gradually formed, Sb(OH) 6- Diffusion takes a long time to reach the adsorption site, which is controlled by the mass transfer within the particle. Assuming an infinite mass transfer rate, when the adsorption breakthrough point is reached, the adsorption breakthrough curve will be perpendicular to the X-axis. Figure 7In (c), 0.1M HCl was used to elute a single adsorption bed, and the treatment volume to achieve complete decomposition was 70BV, i.e. 102mL. This means that 1838mL of antimony-containing wastewater can be treated by a single column while consuming 102mL of eluent. The above results verify that metal organic framework adsorption materials can be used as adsorbents to treat actual Sb(OH) 6- Suitability of wastewater.
[0062] (2) Three short-term fixed beds filled with metal organic framework adsorbents in series
[0063] Three single fixed adsorption beds were connected in series as a whole to evaluate the adsorption of Sb(OH) 6- Wastewater treatment effect. Figure 8 (a) is a schematic diagram of treating antimony-containing aqueous solution by connecting three metal organic framework adsorption material fixed beds in series. Figure 8 (b) shows the adsorption breakthrough curve of wastewater treated by three columns in series, with an initial concentration of 200 μg L -1 , the flow rate is 1.93 cm / min, the empty bed contact time is 0.570 min, when the concentration of the effluent reaches Sb(OH) 6- The maximum allowed emission pollution concentration is 6μg L -1 , that is, when the breakthrough point C / C0 = 0.03, the three-column bed in series can process Sb(OH) 6- The volume is about 1440BV, or 6303mL. At the point of complete adsorption saturation, i.e., exhaustion point C / C0=0.95, the volume that can be processed by the three-column bed in series is about 2210BV, or 9673mL. The processing volume of the three-column bed in series, 6303mL, is 3.43 times the processing volume of the single-column adsorption bed, 1838mL. The three-column bed in series can more thoroughly utilize the metal organic framework adsorption material to remove Sb(OH) 6- As time goes by, the adsorption is concentrated in different areas of the adsorption bed, and the sufficient contact enhances the mass transfer inside the particles, thereby improving the utilization of adsorption sites. Sb(OH) adsorbed on Bi-MOF 6- It can be completely resolved with 0.1M HCl solution, and the processing volume is about 85BV, i.e. 372mL. The results are as follows Figure 8 As shown in (c), the total empty bed contact time of the three-column bed in series is 1.71 min. It can be deduced that the total bed volume of the three-column bed in series is 4.377 mL, and 842 BV, or 3686 mL of Sb(OH) can be processed every day. 6- Wastewater. For such small columns, it is satisfactory to be able to treat such a large volume of wastewater. The use of such cascaded adsorption beds can provide a simple and effective process for the efficient removal of adsorbents in actual industrial wastewater.
[0064] In summary, the present invention uses soluble bismuth salt as a metal source and trimesic acid as a connecting ligand to prepare a metal organic framework adsorbent material with specific pocket-type capture channels through a solvent thermal reaction. The porous organic framework adsorbent formed by the present invention has a high charge density of cationic Bi 3+ The high coordination number and flexible coordination mode of the metal organic framework adsorption material have the ability to match Sb(OH) 6- The pore structure of the size is conducive to Sb(OH) 6- The metal organic framework adsorption material with a high proportion of open pocket capture channels is developed based on the inherent structural properties of the material itself to form Bi-O-Sb bonds and be selectively captured. 6- Targeted capture to achieve a dual improvement in adsorption capacity and selectivity.
[0065] It should be noted that when the present invention relates to a numerical range, it should be understood that the two endpoints of each numerical range and any value between the two endpoints can be selected. Since the steps and methods used are the same as those in the embodiments, in order to avoid redundant description, the present invention describes a preferred embodiment. Although the preferred embodiments of the present invention have been described, once those skilled in the art know the basic creative concept, they can make other changes and modifications to these embodiments. Therefore, the attached protection scope is intended to be interpreted as including the preferred embodiment and all changes and modifications that fall within the scope of the present invention.
[0066] Obviously, those skilled in the art can make various changes and modifications to the present invention without departing from the spirit and scope of the present invention. Thus, if these modifications and variations of the present invention fall within the scope of the protection scope of the present invention and its equivalent technology, the present invention is also intended to include these changes and variations.
Claims
1. A method for preparing a metal organic framework adsorption material, characterized in that: The following steps are involved: In an organic solvent, a metal-organic framework adsorption material with specific pocket-type capture channels is prepared by solvothermal reaction using soluble bismuth salt as the metal source and trimesic acid as the connecting ligand.
2. The method for preparing a metal organic framework adsorption material according to claim 1, characterized in that: The mass ratio of the soluble bismuth salt to trimesic acid is 1:1-5.
3. The method for preparing a metal organic framework adsorption material according to claim 1, characterized in that: The solvent thermal reaction temperature is 120°C to 200°C, and the reaction time is 12h to 72h.
4. The method for preparing a metal organic framework adsorption material according to claim 1, characterized in that: The organic solvent is a mixed solvent of N,N-dimethylformamide and methanol.
5. The method for preparing a metal organic framework adsorption material according to claim 4, characterized in that: In the mixed solvent, the volume ratio of N,N-dimethylformamide to methanol is 1 to 4:
1.
6. The method for preparing a metal organic framework adsorption material according to claim 1, characterized in that: The soluble bismuth salt is Bi(NO3)3·5H2O.
7. A metal organic framework adsorption material obtained by the preparation method according to any one of claims 1 to 6.
8. The metal organic framework adsorption material according to claim 7, characterized in that: The metal organic framework adsorption material is a hexagonal rod structure.
9. A metal organic framework adsorption material according to claim 7 for efficiently and selectively capturing Sb(OH) in antimony-containing wastewater 6- Application in.
10. The use according to claim 9, characterized in that: The concentration of the antimony-containing wastewater is 50 mg / L to 2000 mg / L, and the dosage ratio of the metal organic framework adsorption material to the antimony-containing wastewater is 1 mg: 1 mL to 4 mL.
Citation Information
Patent Citations
Preparation method of selenite radical-adsorbing adsorbent with high efficiency and high selectivity
CN108273472A
Rare-earth-element-doped defective UiO-66 material as well as preparation method and application thereof
CN113019331A
Metal-Organic Frameworks for Adsorption of Liquid Phase Compounds
US20180134581A1